Early-pregnancy maternal body mass index is associated with common DNA methylation markers in cord blood and placenta: a paired-tissue epigenome-wide association study - Nidhi Ghildayal; Ruby Fore; Sharon M. Lutz; Andres Cardenas; Patrice Perron; Luigi Bouchard; Marie-France Hivert (Epigenetics, 2022)
Women entering pregnancy with elevated body mass index (BMI) face greater risk of adverse outcomes during pregnancy, delivery, and for their offspring later in life, potentially via epigenetics. If epigenetic programming occurs early during in utero development, the differential marks should be detectable in multiple tissues despite the known unique epigenetic profile in each. We used early-pregnancy BMI as reflection of maternal metabolic milieu exposure in peri-conception and early-pregnancy period. We analysed DNA methylation in paired cord blood and placenta samples among 437 newborns from Gen3G, a pre-birth prospective cohort of primarily European descent. We measured DNA methylation in both tissues across the genome in >720,000 CpG sites using the Illumina MethylationEPIC array. At each site, we used linear mixed models (LMMs) with an unstructured variance-covariance matrix to test for an association between maternal early-pregnancy BMI and DNA methylation in both tissues (modelled as M-values). We adjusted for tissue-specific covariates, offspring sex, gestational age at delivery, and maternal smoking and age. Women had a mean (SD) BMI of 25.4 (5.7) kg/m2 measured at first trimester visit (mean=9.9 weeks). Early-pregnancy BMI was associated with differential DNA methylation levels in paired-tissue analyses at two sites: cg10593758 (β=0.0126, SE=0.0025; P=4.07e-7), annotated to CRHBP, and cg0762168 (β=−0.0094, SE=0.0018; P=2.78e-7), annotated to CCDC97. Application of LMMs in DNA methylation data from distinct fetal-origin tissues allowed us to identify CpG sites at which early-pregnancy BMI may have an epigenetic ‘programming’ effect on overall fetus development. One site (CRHBP) may play a role in hypothalamic-pituitary-adrenal axis regulation.